EJBot-II: an optimized skid-steering propeller-type climbing robot with transition mechanism. (18th October 2019) - Alkalla, Mohamed G.; Fanni, Mohamed A.; Mohamed, Abdel− Fattah; Hashimoto, Shuji; Sawada, Hideyuki; Miwa, Takanobu; Hamed, Amr
Abstract : This paper presents a new kind of climbing robots called EJBot, which has not been restricted to climb certain surface materials or terrains. EJBot is inspired by propeller-based aviation systems, however, its adhesion principle is opposite to flight concept. Thanks to the hybrid actuation system embedded in this robot which gives a good and stable adhesion. This hybrid system consists of propeller thrust forces and wheel torques actuated simultaneously to generate the proper adhesion force. It is similar to a car climbing a ramp, it needs both weight of the car and the wheels' torques. Without these torques, the car will roll down. Consequently, the thrust forces of the propellers increase the traction force capacity, then the wheels' role arises to generate the convenient torques for stopping the robot or navigating it on the structures. The feasibility of this adhesion concept is verified by the first and second modules of EJBot as presented in the simulation and practical results. GRAPHICAL ABSTRACT: